2018
DOI: 10.4028/www.scientific.net/kem.788.3
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Silica Fume Source on Crystallization of Xonotlite in a New Process Making Medium Density Ca-Silicate Based Products

Abstract: This paper investigates the influence of different types of silica fume on the crystallization process of medium density calcium silicate based products. The products are formed by a new technology that consists of two steps. In the first step, a mixture containing calcium silicate hydrates (C-S-H) is formed by reaction of lime with special silicas at temperatures below 100°C. This mixture is then molded into boards by a filter-pressing technique. In the second step, the boards are treated in hydrothermal cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…( 8) and ( 9) are the compositionstructure relationships where charge compensation of the substitution of Al 3+ for Si 4+ ions is entirely by alkali cations or Ca 2+ ions, respectively. The close relationship between Richardson and Groves's formulation and the models due to Taylor [16], Cong and Kirkpatrick [21,22], Nonat and Lecoq [23] and Chen et al [1] has been demonstrated by Richardson [6]. Glasser et al's [24] and Stade's [15] models are closely related.…”
Section: Calcium Silicate Hydrate (C-s-h) Gelsmentioning
confidence: 85%
See 4 more Smart Citations
“…( 8) and ( 9) are the compositionstructure relationships where charge compensation of the substitution of Al 3+ for Si 4+ ions is entirely by alkali cations or Ca 2+ ions, respectively. The close relationship between Richardson and Groves's formulation and the models due to Taylor [16], Cong and Kirkpatrick [21,22], Nonat and Lecoq [23] and Chen et al [1] has been demonstrated by Richardson [6]. Glasser et al's [24] and Stade's [15] models are closely related.…”
Section: Calcium Silicate Hydrate (C-s-h) Gelsmentioning
confidence: 85%
“…This C-S-H present in hardened pastes of C3S/ C2S or neat Portland cements generally has a mean Ca/Si ratio of about 1.75, with a range of values within a given paste from around 1.2 to 2.1 [5]. Higher values of Ca/Si in the literature could be explained by mixtures of C-S-H with portlandite, Ca(OH)2 [1]. Unlike the highly crystalline hydrated calcium silicate phases, some people associate the C-S-H gel term as a nearly amorphous or even amorphous material.…”
Section: Calcium Silicate Hydrate (C-s-h) Gelsmentioning
confidence: 94%
See 3 more Smart Citations